Magija reči u pripoveci Momčila Nastasijevića „Zapis o darovima moje rođake Marije” - Žižović, Olivera (Wydawnictwo Naukowe UAM, 2013)
Interpretation of Momčilo Nastasijević’s narrative „An Account of the Gifts of my Cousin Marija” indicated the significance of the storyteller’s belief in the magic of words and in calamitous effect of words on destiny – not only his own destiny, but also that of his cousin Marija. Except the power of words – curse, and magic belief in it, important part in the events is also played by disrespect for somebody else’s word (intensified by the fact that it is the last will of a dying person), as well as by breaking of one’s word (false oath), which also turns to be fatal. Destiny of Marija and that of her cousin is viewed from the perspective of depth psychology, as well as her confronting individual and collective Shadow, and his temporary state of being overwhelmed, and later permanently engulfed by unconscious contents and family Shadow. While Marija comprehends evil in herself and in the world, and through agony and suffering reveals her light side, and experiences enlightenment, her cousin, having heard her story, begins to identify himself with dead Marija, failing to face these contents or fight them creatively. Marija has „light in her life” while expecting the second coming of Christ – coming of the Word, Logos, that will set the world free, so she spends her life doing embroidery, in order to fulfill the Word – what was foretold and announced (spoken and written). Unlike her, under the pressure of his cognition, her cousin falls silent, wishing only for death, which is the only one, he believes, that can untie the knot of his suffering. Still, in order to die peacefully, actually to be able to die at all, near the end of his life he will be compelled to speak, meaning to write down the narrative about his cousin and himself, in order for the „knot of suffering” to be resolved by words, meaning, by the very concept that tied it in the first place.
Magic of Words in Momčilo Nastasijević’s Narrative "An Account of the Gifts of My Cousin Marija"
Keywords: Momčilo Nastasijević; magic of words; depth psychology; curse; Shadow; Christ the Savior; Logos; second coming